The Tasks of the Intermediate Schoolmasters in Reference to Time Administration according to Headmaster's Viewpoint - استبرق محمد مهدي Estabraq Mohammed Mahdi (College of Education for Women, 2018)
The aim of this research is to recognize the tasks undertaken by   the   headmasters   of   intermediate   schools   concerning   time- administration,   in   accordance   to   the   viewpoints   of   the headmasters   of   intermediate   schools   in   the   Administration   of Education   of   Al-Karkh   the   Third.   The   sample   of   this   research consists   of   (60)   headmasters   and   headmistresses   and   the   tool used on this research was the 'questionnaire.' The results of the research   showed   that   in   any   task   undertaken   by   headmasters without considering time is only a waste and in vain. The correct planning of the task that reconsiders time makes the work more balanced. It is noteworthy that time assigned for a task must be divided   correctly   according   to   the   plans   put   whether   they   are annual or 5-year plans. Also, considering time in any educational planning makes work more disciplined and away from any chaos. According to these results, the research comes up with a number of suggestions and proposals.